Management of Rapidly Progressing Periodontitis: An Overview (Medicine Today, 2017)
History of periodontal diseases recognition and treatment is ancient for at least 5000 years. There are different presentations of periodontal diseases. Rapidly progression periodontitis or aggressive periodontitis causes rapid destruction of the periodontium which leads to early tooth loss. It may be generalized or localized. Periodontitis may be treated surgically or non-surgically but patients with rapidly progressing periodontitis do not respond predictably to conventional therapy due to its multi factorial etiology. Successful management of the disease is difficult if not diagnosed early and treated appropriately. Regenerative therapy, tissue engineering and genetic technologies are the new hope for the treatment of rapidly progressing periodontitis.Medicine Today 2016 Vol.28(1): 32-38